(untitled) (Mediscope, 2024)
Background: Magnesium has been considered an important factor in the pathogenesis of acute myocardial infarction and its complications. Magnesium ions are essential for the maintenance of the functional integrity of the myocardium. It also improves vascular tone, afterload and cardiac output, and decreases peripheral vascular resistance and cardiac arrhythmias. Serum magnesium concentration has great significance in the prognosis of acute myocardial infarction (MI). Aim and objective: This study aimed to assess the relation of low serum magnesium levels with post-infarction complications of acute MI. Methods: This cross-sectional descriptive study was conducted in the Department of Pharmacology & Therapeutics, Rajshahi Medical College in collaboration with the Cardiology department between July 2019 to June 2020. Assessment and comparison of the serum magnesium level of the patients on the 5th day of post-infarction with the 1st day of admission in 50 patients of acute MI was done in this study. Results: The mean magnesium level was 2.25 ± 0.15 mg/dl in patients without any complications which was significantly higher than the patients who had multiple complications. The level of magnesium was 1.79 ± 0.37 mg/dl in complicated cases. (P˂0.001). These observations suggest that in acute myocardial infarction, patients with low magnesium levels are more prone to develop complications. Conclusion: So it can be concluded that measurement of serum magnesium levels has prognostic significance and magnesium treatment can be implicated in patients of acute myocardial infarction with low magnesium levels. Mediscope 2024;11(1): 27-33